Detection and Analysis of Batik Waste Using Image Processing Methods in Pekalongan Regency - Tachriri, Yusril Ihza; Agustina, Elvinda Bendra; Rachman, Dian Arif; Sari, Atika Windra; Karimah, Imroatul; Artamevira, Jessika (LPPM Universitas Dian Nuswantoro, 2025)
Research was conducted on the detection of batik wastewater in the batik industry of Pekalongan, which generates liquid waste containing synthetic dyes, heavy metals, and hazardous compounds that can potentially pollute the environment if not properly treated. This study aims to develop a simple detection method based on digital image analysis to identify the color characteristics of batik wastewater. Data were obtained by sampling liquid waste from several affected rivers, which were then analyzed using a digital camera and image processing software to determine the intensity values of the red, green, and blue (RGB) channels. The results show that variations in waste concentration significantly influence the distribution of RGB values, enabling faster, cheaper, and more practical identification of pollution patterns compared to conventional laboratory methods. These findings are expected to serve as the foundation for developing a digital technology-based batik wastewater quality monitoring system as part of efforts to mitigate environmental pollution in Pekalongan. Keywords - Batik wastewater, Digital image analysis, RGB intensity, Environmental pollution, Image processing